Synthesis and study of metal-based oxygen carriers (Cu, Co, Fe, Ni) and their interaction with supported metal oxides (Al2O3, CeO2, TiO2, ZrO2) in a chemical looping combustion system - Tijani, M.M. (Elsevier Ltd, 2017)
Methane-fueled chemical looping combustion was investigated using transition metals (Cu, Co, Fe, Ni) that were deposited on support oxides (Al2O3, CeO2, TiO2, ZrO2) as oxygen carriers to find potential oxygen carrier candidates that had less interaction between the active-sites and supports. Less interaction between the active-sites and supports could help increasing the selectivity of CO2 among other gases (CO, H2) and to reduce the solid inventories in the CLC reactor system. The results showed that the average particle size for the synthesized samples was in the range of 8–119 nm. The effect of the sample initial weight in the TGA showed no significant effect on the oxidation/reduction reactions of metals. As the CH4 concentration increased, the reduction rate of oxygen carriers and coke formation increased. Highest oxygen detachment of supported oxygen carriers was reported to be 3.12 for Cu/CeO2 at 900 °C, 6.14 for Co/TiO2 at 950 °C, 6.83 for Fe/CeO2 at 950 °C, and 5.00 for Ni/CeO2 at 950 °C. Support oxides showed a significant effect on the oxidation and reduction activation energies, where Cu/Al2O3, Co/CeO2, Fe/ZrO2, and Ni/ZrO2 samples showed an improved performance among other combinations. © 2017 Elsevier Ltd